Clinical Characteristics and Outcomes of COVID-19 Patients with Overweight and Obesity: Turkish Nationwide Cohort Study (TurCObesity) - Sahin, Ibrahim; Haymana, Cem; Demir, Tevfik; Demirci, Ibrahim; Tasci, Ilker; Atmaca, Aysegul; Cakal, Erman; Ata, Naim; Emral, Rifat; Unluturk, Ugur; Ertugrul, Derun; Salman, Serpil; Sahin, Mustafa; Dagdelen, Selcuk; Celik, Osman; Caglayan, Murat; Satman, Ilhan; Sonmez, Alper (Experimental and Clinical Endocrinology & Diabetes, 2021)
Purpose While obesity is related to more severe outcomes of coronavirus disease 2019 (COVID-19), factors leading to poor prognosis still remain unclear. The present study evaluated the outcomes of COVID-19 patients who were overweight or obese and variables associated with severe disease in a large group of consecutive cases.Methods A nationwide retrospective cohort study was performed using the Turkish National Healthcare Database. Demographic characteristics, laboratory tests, comorbidities, and medications of patients registered between March 11 and May 30, 2020, were recorded.Results A total of 14, 625 patients (median age:42, IQR:26 years; female 57.4%) with normal weight (34.7%), overweight (35.6%), and obesity (29.7%) were included. Hospitalization, ICU admission, intubation/mechanical ventilation, pulmonary involvement, and mortality were significantly higher in patients who were overweight or obese. In adjusted analyses, both overweight (OR, 95% CI: 1.82, 1.04–3.21; p=0.037) and obesity (OR, 95% CI: 2.69, 1.02–1.05; p<0.001) were associated with a higher intubation/mechanical ventilation rate but only obesity was associated with increased mortality (OR, 95% CI: 2.56, 1.40–4.67; p=0.002). Old age, male gender, chronic kidney disease, and high C reactive protein levels were independently associated with COVID-19 mortality in overweight or obese patients.Conclusions COVID-19 patients who were overweight or obese were more likely to have adverse outcomes but only obesity was a predictor of mortality. Such patients should receive urgent medical attention and active management, especially the elderly, men, and people with chronic kidney disease.
Keywords: Obesity; overweight; COVID-19; morbidity; mortality